Early Positive Brain 18F-FDG PET and Negative MRI in Rasmussen Encephalitis. (10th March 2023) - Thomé, Ursula; Machado, Hélio Rubens; Santos, Marcelo Volpon; Santos, Antonio Carlos; Wichert-Ana, Lauro
Abstract: A 15-year-old adolescent boy with left body epilepsia partialis continua, hemiparesis, and electroencephalogram abnormalities lateralized to the right hemisphere. MRI finding was small hyperintense signal in the left putamen. 18 F-FDG PET showed focal glucose hypermetabolism in the right paracentral lobule and hypometabolism in the inferior right frontal and precentral gyri. One month later, a new MRI showed a hyperintense signal over the paracentral lobule. Biopsy on this region confirmed the diagnosis of Rasmussen encephalitis. This patient finally underwent right hemispherotomy and became seizure free. This case emphasize the PET as an important early tool for the diagnosis of Rasmussen encephalitis.